Movement system variability - Newell, Karl M. 1945-; Bennett, Simon; Davids, K. 1953- (Keith). (Champaign, IL Human Kinetics, 2006)
In the groundbreaking text, Movement System Variability, internationally known scientists synthesize the latest research in the study of variability in the human movement system and provide an in-depth, multi-disciplinary analysis for researchers in human movement sciences and related fields. Movement System Variability's unique dynamic systems perspective in most chapters adds a new theoretical interpretation to the role of variability in movement behavior. A rich array of scientific disciplines is represented in the text to offer insights into the nature and role of variability observed at different levels of analysis. Movement System Variability is organized into five parts: Behavioral Analysis of Variability in the Movement System; Variability, Performance and Excellence; Issues in Measurement; Variability Across the Lifespan; Variability Within Subsystems. This essential reference book provides fresh insights into the nature and function of variability. Just as important, it demonstrates how an understanding of variability can enhance the practice of educators, teachers, coaches, physiotherapists, and developmental specialists. This book is an ideal reference for researchers or students interested in the human movement sciences.
Part I. Behavioral Analysis of Variability in the Movement System -- Chapter 1. Variability in Motor Output As Noise: A Default and Erroneous Proposition? / Karl M. Newell, PhD, Katherine M. Deutsch, PhD, Jacob J. Sosnoff, PhD, and Gottfried Mayer-Kress, PhD ; Noise and Movement Variability in Information Theory ; Noise in Physiological Models of Motor Control ; Categories of Noise ; Variability and Noise in Motor Output ; Multiple Time Scales of Variability ; Concluding Comments -- Chapter 2. Variability in Postural Coordination Dynamics / Olivier Oullier, PhD, Ludovic Marin, PhD, Reinoud J. Bootsma, PhD, Thomas A. Stoffregen, PhD, and Benoît G. Bardy, PhD ; Ambiguity of the Neurophysiological Approach to Postural Coordination ; Kinematic Analysis of Dynamic Patterns in Postural Coordination ; Postural Coordination Emerges from the Interplay of Different Constraints ; Intention (to Sway) Modulates the Stability of Postural Coordination ; Dynamics of Postural Transitions ; Nature of the Transitions Between Postural Coordination Patterns ; Variability in Self-Organization of Postural Coordination ; Unique Aspects of Postural Coordination ; Conclusion ; Acknowledgements ; Footnotes -- Chapter 3. The Interface of Biomechanics and Motor Control: Dynamic Systems Theory and the Functional Role of Movement Variability / Paul S. Glazier, Jonathan S. Wheat, PhD, David L. Pease, and Roger M. Bartlett, PhD ; Movement Variability: Traditional and Contemporary Approaches ; Biomechanics and Motor Control ; Sports Biomechanics: A Critical Overview ; Dynamic Systems Theory Applied to Sport Biomechanics ; Concluding Remarks -- Part II. Variability, Performance and Excellence -- Chapter 4. Serving Up Variability and Stability / Craig Handford, PhD ; Deliberate Practice Is Not Always About Movement Consistency ; Solutions to Movement Problems Can Be Generic and Yet Individual ; Variability Can Provide a Basis for Practice in Parts ; Conclusion -- Chapter 5. Variability in Motor Output and Olympic Performers / Les G. Carlton, PhD, John W. Chow, PhD, and Jaeho Shim, PhD ; Variability in the Motor Domain ; Speed and Accuracy in Projectile Tasks ; Models of Throwing Accuracy ; Throwing Accurately to Horizontal Targets ; Throwing Accurately to Vertical Targets ; Speed-Variability Trade-Offs in Sport Tasks ; Speed and Variability in Throwing Tasks ; Speed and Variability in Striking ; Summary ; Olympic Project ; Data Collection ; Location of Ball Landing ; Ball and Racket Speeds ; The Olympic Project and Speed-Accuracy Trade-Offs -- Chapter 6. Genetic and Environmental Constraints on Variability in Sport Performance / Joe Baker, PhD and Keith Davids, PhD ; Nurture Perspective of Expertise Development: Deliberate Practice ; Challenges of Deliberate Practice ; Genetic Constraints on Physical Performance ; Genetic Contribution to Motor Skill Performance ; Genetic Contribution to Variability in Physical Performance ; Concluding Remarks: A Case for Dynamic Systems Theory -- Part III. Issues in Measurement -- Chapter 7. Coordination Profiling of Movement Systems / Chris Button, PhD, Keith Davids, PhD, and Wolfgang Schöllhorn, PhD ; Theoretical Evolution of Variability in Movement ; Data Collection and Statistical Analysis ; Coordination Profiling ; Cluster Analyses and Time-Continuous Variables of Intra- and Interindividual Athletic Performance ; General Discussion and Implications -- Chapter 8. Clinical Relevance of Variability in Coordination / Joseph Hamill, PhD, Jeffrey M. Haddad, MS, Bryan C. Heiderscheit, PhD, Richard E.A. Van Emmerik, PhD, and Li Li, PhD ; Variability in Traditional and Dynamical Systems View ; Dynamic Systems Concept of Variability in Movement ; Clinical Relevance of Variability ; Conclusions -- Chapter 9. Measuring Coordination and Variability in Coordination / Jonathan S. Wheat, PhD and Paul S. Glazier, PhD ; Measuring Coordination and Variability in Coordination ; Summary -- Part IV. Variability Across the Lifespan -- Chapter 10. Functional Variability in Perceptual Motor Development / Geert J.P. Savelsbergh,PhD, John van der Kamp, PhD, and Karl S. Rosengren, PhD ; Functional Coupling of Perception and Movement: Constraints ; Variability in Early Infant Reaching ; Functional Variability and Exploration ; Variability and Selection in the Coupling of Information and Movement ; Conclusions -- Chapter 11. Aging and Variability in Motor Output / Evangelos A. Christou, PhD and Brian L. Tracy, PhD ; Older Adults Do Not Always Exhibit Greater Variability in Motor Output Within a Trial ; Older Adults Exhibit Greater Variability in Motor Output From Trial to Trial ; Physical Training Attenuates the Variability of Motor Output in Older Adults ; Changes in the Nervous System Alter Variability in Motor Output ; Summary -- Part V. Variability Within Subsystems -- Chapter 12. Mechanical Properties of Muscles Reduce Performance Variability / Alberto Minetti, MD ; Arm Wrestling ; Variability in Drop Landing ; Conclusions -- Chapter 13. Cellular and Molecular Basis of Heterogeneity in Contractile Performance Variability / Carlo Reggiani, PhD and Susan Bortolotto, PhD ; Functional and Molecular Heterogeneity of Muscle Fibers ; Functional Characterization of Human Muscle Fiber Types: Contractile Properties ; Heterogeneity of Electrophysiological Properties and Excitation-Contraction Coupling in Human Muscle Fibers ; Metabolic Heterogeneity of Human Muscle Fibers ; Plasticity of Human Skeletal Muscles ; Optimization of Muscle Performance by Selective Recruitment ; Conclusions -- Chapter 14. Self-Organizing Brain Dynamics and Movement Goals / Walter Freeman, MD ; Limbic Contributions to Intentional Action ; Neurodynamics of Chaos in Perception ; Conjoining of Time and Space Through Action ; Linear Causality Versus Circular Causality ; Timing in the Awareness of Action ; Conclusion -- Chapter 15. Variability of Brain Activity During Rhythmic Unimanual Finger Movements / T.D. Frank,PhD, C.E. Peper, PhD, A. Daffertshofer, PhD, and P.J. Beek, PhD ; Theoretical Framework ; Coordinated Rhythmic Movements ; Experiments and Experimental Results ; Dominance of Descending Neural Activity ; Phase Synchronization and Mean-Field Forces ; Connectivity Maps ; Mean-Field Haken-Kelso-Bunz Model ; Implications for the Dynamic Systems Approach ; Outlook.
Includes bibliographical references
Keywords: Human locomotion; Musculoskeletal system -- Variation; Different pathways -- Variation